Intensi Kewirausahaan Petani Milenial di Sentra Produksi Sayuran Kabupaten Bangka: Theory of Planned Behavior: Entrepreneurial Intention of Millennial Farmers in the Vegetable Production Center of Bangka Regency: Theory of Planned Behavior - Rufti Puji Astuti; Tri Lestari; Aimie Sulaiman (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Millennial farmers are part of the farmer regeneration acceleration program aimed at increasing the number of farmers and expanding the supply of entrepreneurs in the agricultural sector. This study was conducted to predict the behavior of millennial farmers through their intentions, based on the Theory of Planned Behavior (TPB), comprehensively integrating individual aspects with their environment. The purpose of the study is to analyze the factors that influence the entrepreneurial intentions of millennial farmers. The research method employed a survey method, with sampling carried out using a saturation sampling method involving 54 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) analysis utilizing Smart Partial Least Squares (PLS) 3.0. The research findings revealed that 81.49% of millennial farmers have entrepreneurial intentions, specifically in agriculture. Entrepreneurial intention is significantly influenced by variables such as attitude toward the behavior, subjective norms, and perceived behavior control. The entrepreneurial intention of millennial farmers is predominantly influenced by attitude toward the behavior and subjective norms. For millennial farmers deciding to venture into entrepreneurship, relying solely on the importance of belief and self-evaluation is not enough; the motivation and desire to meet expectations also play a crucial role in enhancing intention.